COMPARISON OF FLUTICASONE NASAL SPRAY AND ORAL MONTELUKAST FOR THE TREATMENT OF SEASONAL ALLERGIC RHINITIS IN CHILDREN 8 YEARS TO 15 YEARS OF AGE (The Research of Medical Science Review, 2025)
Background: Seasonal allergic rhinitis (SAR) is a common condition in children, characterized by inflammation of the nasal mucosa due to allergens, leading to symptoms such as sneezing, rhinorrhea, nasal congestion, and itchy eyes. Effective management is essential to improve children's quality of life. Objective: This study aimed to compare the efficacy of fluticasone nasal spray and oral montelukast in treating SAR in children aged 8 to 15 years. Study Design: A randomized controlled trial. Study Setting: The research was carried out at Sialkot Medical College, Sialkot from 2 August 2024 to 2 February 2025. Methodology: A total of 60 children diagnosed with SAR were enrolled in the study after obtaining informed consent from their parents. Participants were randomly assigned to two groups: Group A received fluticasone propionate nasal spray (100 micrograms in each nostril once daily), while Group B received oral montelukast tablets (5 mg daily in the evening) for four weeks. Symptom severity was assessed using a scoring system that evaluated sneezing, rhinorrhea, nasal congestion, and other related symptoms. Data were collected at baseline and after four weeks of treatment, and statistical analysis was performed using SPSS software to compare the mean differences in nasal scores between the two groups. Results: A majority of participants were male 36 (60%) and 24 females (40.0%), Fluticasone Nasal Spray demonstrated significantly greater efficacy than Montelukast, with 80% of participants in the Fluticasone group showing symptom improvement compared to 60% in the Montelukast group (p=0.035). Subgroup analysis showed no significant differences in efficacy based on age or gender, but a significant difference was observed in patients with severe initial clinical scores (p=0.029). Conclusion: Our study demonstrates that Fluticasone Nasal Spray is significantly more effective than Montelukast in relieving symptoms of Seasonal Allergic Rhinitis in children. The findings support the use of Fluticasone as a preferred treatment option for managing SAR in this population.